ABC proteins in evolution. Issue 23 (13th October 2020) - Ogasawara, Fumihiko; Kodan, Atsushi; Ueda, Kazumitsu
Abstract : ATP‐binding cassette (ABC) proteins play diverse roles in all living organisms, making them an attractive model for evolution. Early evolution of ancestral unicellular organisms entailed the acquisition of at least three types of ABC proteins: type 1 ABC proteins to import nutrients, and type 2 and 3 ABC proteins to generate the outer cell membrane by flopping and loading lipids onto acceptors, respectively. To export various toxic lipophilic compounds, cells evolutionarily acquired a fourth type of ABC protein. This suggests that ABC proteins may have played an important role in evolution, especially when life became terrestrial, protecting plants and animals from water loss and pathogen infection. ABC proteins are also assumed to have accelerated the evolution of vertebrates by allowing cholesterol to function for intramembrane signaling. In this review, we discuss the roles of ABC proteins in the evolution of bacteria, plants, and animals.